Internship Partners for Long-Term Care Administrators – A Model Sustainable Through COVID-19 Is a Model for the Future (Journal of Organizational Psychology, 2021)
Most long-term care administration programs require an internship as a graduation requirement. The University of Wisconsin – Eau Claire’s Health Care Administration interns are highly valued by partner sites, hosting students annually. In the 2019-2020 academic year, 59 students were nine months into their internship experience when COVID-19 disruptions became widespread. This paper describes the program’s immediate and multifaceted response, which led to exceptional outcomes. Lessons learned suggest that through effective planning and exceptional reaction in the face of adversity, strong academic programs and partnerships play a key role in alleviating long-term care workforce challenges by producing extraordinarily prepared future leaders.
Keywords: organizational psychology; COVID-19; long-term care; workforce; pandemic response; internship